Peningkatan Peran Wakil Presiden Melalui Keppres No. 121 Tahun 2000 - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2000)
The issuance of the Presidential Decree No. 121,2000 about sharing duties of the President to the vice president in conducting the techniques of managing daily governmental affairs constitutes a real effort to optimize the vice president's role and ministerial works which have so far been considered very weak. However, this decree could be as warning signal for the vice presiden Megawati to prove hercapability, whether or not she is able to run the government well.